Measuring inequalities in the distribution of health workers by bi-plot approach: The case of Turkey - Alkan, B. Baris; ., Afsin Sahin (Journal of Economics and Behavioral Studies, 2011)
Optimal planning of the health workers is of vital importance for a country. Distribution of health workers among provinces in emerging markets is an important development criterion. In this study, biplot graphical approach is used to determine the distribution of health workers. The results of biplot analysis point out that the distribution of the healthcare staff in Turkey is unbalanced. The number of health workers should be planned and considered according to the desire, need, population, target and workload criteria. The new employment opportunities should be created and the workers should be encouraged to serve in low income regions by providing better conditions.